Activity‐Stability Volcano Plots for Material Optimization in Electrocatalysis. Issue 14 (21st June 2019) - Exner, Kai S.
Abstract: In the last two decades, research in electrocatalysis has been spurred by theoretical calculations and predictions based on the concept of ab initio thermodynamics, which has become a valuable tool for computational researchers in material screening. These investigations most commonly result into the construction of activity‐based volcano plots in order to predict potential electrocatalysts for the application in practice. However, the prototypical activity‐based volcano concept neither captures the influence of the applied overpotential on the activity nor the stability of electrode surfaces. Herein, the well‐established volcano approach is expanded by constructing activity‐stability volcano plots, which, beside the activity, also enclose the stability and the applied overpotential into the analysis. Abstract : Overpotential matters : The construction of an activity‐stability volcano plot for the chlorine evolution reaction over RuO2 (110) reveals that an increase in overpotential shifts the optimum performance from strong oxygen binding to weak oxygen binding.